Production of Cellulose and Profile Metabolites by Fermentation of Glycerol by Gluconacetobacter Xylinus - Vidotto,Francielle Lina (2018)
ABSTRACT Because of the widespread occurrence of cellulose in nature, many organisms use glycerol as a source of carbon and energy, so these organisms have drawn attention to the potential use of glycerol bioconversion. The bacteria Gluconacetobacter xylinus, a strictly aerobic strain that performing incomplete oxidation of various sugars and alcohols to cellulose biosynthesis. For this reason, we modify the Hestrim-Schram medium, associating glycerol, glucose and sucrose varying their concentration. The fermentations were performed statically at a temperature of 28˚C for a period of 10 days. The pH, membrane formation, crystallinity and the production of some metabolites of the 4th, 7th and 10th days was evaluated. The results showed a higher yield of membrane in the medium containing glucose, gly 1 + glu2 on 10 fermentation of 3.5 g %. Through solid-state NMR gave the crystallinity of the membranes, where there was a clear trend toward higher crystallinity membranes with 7 days of fermentation. Metabolic products found in the media by analysis of NMR spectroscopy in liquid were similar, especially for the production of alanine and lactate that were present in all media. The leucine and threonine were present in various media, although in small quantities has been found glutamate.